Uji ketahanan tubuh ikan Nila (Oreochromis Niloticus) yang diberi pakan mengandung ekstrak daun Ciplukan (Physalis angulata L) di pH air rendah - Rustiana Widaryati (Fakultas Peternakan Universitas Kristen Palangka Raya, 2016)
This study aims to determine the body resistance of tilapia (Oreochromis niloticus) provided feed containing ciplukan (Physalis angulata L) leaf extract tested in low water quality. The study used an experimental method in which fish are given feed containing ciplukan leaf extract at a dose of 25 ml / kg of feed, and then tested in low pH water, to see the survival rate of the fish with a long testing time 2 hours, 4 hours, 6 hours. The results showed that the administration of feed containing leaf extract can increase their endurance ciplukan tilapia, where the highest value in the treatment of 2 hours (95.56%) and the lowest at 6-hour treatment (77.78%). Fish were fed with ciplukan leaf extract at low water quality gives a real impact on the survival rate of fish. The longer testing process led to increase mortality rate. The body resistance of fish can be maintained by adding extracts of ciplukan leaf in feed continuously to provide body resistance to low water quality or water quality changes caused by weather. Key words : Physalis angulata L, tilapia, water quality